(untitled) - Green, Jay P. (Indiana, U.S.A, 1987)
In this A Concise Lexicon to the Biblical Languages, for the first time in any book, Bible students now have a lexicon/dictionary with every one of the original 8,674 Hebrew words, and also every one of the 5,624 Greek words, of the Scriptures included in it. For ninety-five out of the hundred times the Bible student, Pastor, Minister, Preacher, Bible class teacher, or the host of God's saints who study to show themselves workmen unashamed (2 Tim. 2:15), this quick reference, easy-to-use lexicon is a jewel. You will literally wear it out, using it weekly, if not daily.The words are alphabetical in order. This is important with the Hebrew words in particular. For the most used Hebrew lexicon is the Brown-Driver-Briggs Hebrew-Aramaic Lexicon. And one must know the root word to look up Hebrew entries in that lexicon, or else they must have a multi-paged index to it. This brief lexicon can even be used instead of the Brown-Driver-Briggs Lexicon in most of the cases when anyone desires a quick reference to the meaning and grammatical construction of a word.
Keywords: Hebrew language -- Dictionaries -- English